Analisis Hipertensi di Kalangan Mahasiswa Fakultas Kesehatan Masyarakat Universitas Halu Oleo - Wa Ode Salma; Irma Yunawati; Nurnashriana Jufri; Elzalika Aisyiyah Agsya; Ninda Garnawati; Ayu Silpina; Nur Satya Maliany; Zainal Zainal; Claudia Fena Nur (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Blood pressure is the amount of blood flowing through blood vessels, and its normal value is <120/80 mmHg. Unbalanced blood pressure, such as hypertension (>140/90 mmHg) or hypotension (<90/60 mmHg), can be harmful to health. Hypotension causes dizziness and fainting due to inadequate blood supply, while hypertension increases the risk of heart disease, stroke and kidney failure. Hypertension in adolescents is influenced by lifestyle, obesity, stress, sleep duration and family history.